National and International Civilian Protection Strategies in the Israeli-Palestinian Conflict - Spitka, Timea (Springer Nature, 2023)
This open access book examines security and protection within Israel and Palestine, analyzing national and international security strategies that apply to the protection of civilians. The author examines the principles, practices and the perception of protection. Focusing on protection strategies and practices in the Israeli-Palestinian conflict, this book reveals some of the myths and enigmas of national and international protection of civilians. The book moves beyond the current lack of protection strategies to discuss more effective human security focused on prioritizing protection of civilians, use of alternative tools such as community policing and inclusive protection.